The Ararat Fiscal Strategy Model : A Structural Framework for Fiscal Policy Analysis in Armenia - Babajanyan, Victoria (IMF Working Papers; Working Paper ;, 2022)
This paper presents an overview of the Ararat Fiscal Strategy Model (AFSM), which is a structural, New-Keynesian, DSGE, small open economy model with a rich fiscal block that includes several expenditure and revenue instruments, and types of debt. The AFSM is now a formal part of the Ministry of Finance analytical toolkit to do macroeconomic fiscal policy scenario analysis, which feeds into policy discussions, budget planning, and the Medium-Term Expenditure Framework. The model was applied to assses the macroeconomic impact of the "first wave" of the Covid-19 pandemic on the Armenian economy, including the mitigating effects of policy responses. AFSM simulations revealed a potential severe impact in 2020, with declines in GDP and consumption of 12.9 and 11.7 percent, respectively, and a cumulative loss of GDP of 38 percent for the period 2020-2023. They also highlighted a significant fiscal outlook deterioration that would increase public debt-to-GDP ratios by 18.8 percentage points over 2020-23. The package of counter-cyclical fiscal measures of 3.6 percent of GDP, however, was estimated to cushion the 2020 GDP decline by almost 2 percentage points, as well as protect jobs. A second AFSM application related to the 2018 public investment under-execution showed the importance of improving the efficiency of public investment to have positive macroeconomic and fiscal effects.